The percheron horse - Waters, Fred (My University, 1902)
Introduction: In treating this subject I will attempt to take the practical side of it and dwell most upon those points that interest the farmer at present; rather than give a long history of development. The farmer and coachman of today are seeking a heavy with good action, and I will attempt in this paper to show that it is the Percheron they are looking for. It is necessary, in order that you understand the qualities of the Percheron, to give you a short history of this breed, and to tell you what people of England and other places think and have thought for years. I use J.H.Sanders, author of “Breeders’ Gazette” and “Percheron Stud Book”, as my authority on the points of history quoted here. It is well known and understood that all modern breeds of horses trace their origin to the same source, that the horse was indigenous in not a few countries, and that his progenitor was the little prehistoric “Hippus” seems to be as generally understood. Hence we must accept, in attempting to write up the Percheron, that originally he was an evolution from the same common source, and that his present degree of excellence is largely due to natural and arbitrary selection. There originally existed in Europe and Asia five distinct races of wild horses. The white, the bay, the black, the piebald, and the dun. In beauty, spirit, speed, and power of endurance the bay, whose blood now exists in composition of the horse of Flanders and the true bred Percheron, excelled all others. Centuries before Christ these bay horses had found their way into Egypt, and had become domesticated among the nations of parts of Asia and southern Europe. As Rome, as a nation, had paid no attention to systematizing any breed of horses after her conquests of Northern Europe, they were left as void of any improved breed of horses as they had previously been found. This left open for future development an enterprise that was commenced by Charlemagne, who ascended the throne of France 768 A.D., and who caused to be brought from Arabia, where these fleet footed horses still existed in their purity, these bay horses now called “Arabian”. And to establish a strong powerful horse that could easily carry the burly knight of Northern Europe with his coat of mail, his battle axe, and spear, he caused these to be crossed with the ponderous black horses that were indigenous in the valleys of the Rhine and upper tributaries to the Danube, and the central plains of Europe, thus producing a magnificent horse that was a success, to a wonderful degree of perfection, for the purpose for which he was bred.
Citation: Waters, Fred. The percheron horse. Senior thesis, Kansas State Agricultural College, 1902.
Morse Department of Special Collections
Keywords: Equine; Percheron; History; Horses; Theses